RESPONSIBLE FISHERIES MANAGEMENT OF MINI PURSE SEINE IN THE LAMPUNG BAY AREA - Yulia Estmirar Tanjov; Roza Yusfiandayani; . Mustaruddin (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
Lempasing is a Coastal Fishing Port (CFP) which located in Bandar Lampung. It is one of the centers of fisheries activities in the city. One of the fishing gear which operated by most of fishermen in Lempasing is mini purse seine. Mini purse seine fishing activities in the Lampung Bay Area and Lempasing CFP is not in accordance with the conditions of the surrounding waters area. The research was conducted in the Lampung Bay Area and Lempasing CFP, Lampung. This study aims to: 1) determine the status of fisheries resources utilization, 2) to describe the dominant fish caught by mini purse seine. Analysis methods were used in this study namely: 1) Fishing Power Index (FPI), Catch Per Unit Effort (CPUE), and Maximum Sustainable Yield (MSY) to determine the status of fisheries resource utilization. The dominant small pelagic fishes caught were scad fish Selaroides sp., mackerel fish Rastrelliger sp., longnose trevally fish Carangoides chrysophrys. The result showed that Fox model was the best fits models with estimated maximum sustainable yield of 15.5 ton and fishing effort of 992 trip/year for mini purse seine. The longnose trevally fish in lampung bay area in do not exceeded the optimal catch fish condition can be used to sustainably. In these condition is necessary to wisely manage and setting the catches to not exceed the allowable catch of the small pelagic fish, so the stock of small pelagic fish in the Lampung Bay Area can be used sustainably.